ANALYSIS OF THE EFFECT OF SUPERVISION AND WORK FACILITIES ON THE EFFECTIVENESS OF EMPLOYEES IN THE FIRE CONTROL AND TRIBE SAFETY SECTION IN GULKARMAT CITY ADMINISTRATION IN WEST JAKARTA - Muhammad As'ad; Danang Darul Fadli (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2022)
Influences of Supervisory and Facilities work Towards Increasing the effectiveness of the work of employees on a Section fire control and rescue service of the Gulkarmat tribe of West Jakarta. Research was conducted to find out the magnitude of the supervision and Facilities work towards Increasing the effectiveness of the work of employees on a Section fire control and rescue service of the Gulkarmat tribe of West Jakarta. The research methods used in this research are quantitative methods through survey, with a total population of 44 people and the sample is 44 people or saturated sample or census. Based on the analysis with the help of SPSS indicates that: partially t test results show that Oversight has a positive influence and significantly to the effectiveness of the work of the employees, because t count is greater than the t table. Partially the second test result shows that the employment facilities of t have a positive and significant influence to the effectiveness of the work of the employees, because t count is greater than the t table. Free variable monitoring and On-site work jointly tested through trials of F has a positive influence and significantly to the effectiveness of the work of the employees, because F count greater than F table.